THE EFFECT OF PRICE AND ADVERTISING PROMOTION ON THE INTEREST OF ONLINE TRANSPORTATION SERVICE USERS - Royani, Ida; Thaci, Hashim (JMRI Journal of Multidisciplinary Research and Innovation, 2024)
This research aims to analyze the influence of price and advertising promotion on people's interest in using Grab online transportation services. The approach used is a nonprobability sampling technique, namely purposive sampling. The data were statistically analyzed using validity test, reliability test, classical assumption test, multiple linear regression, and determination test (R2). The data source used in this study is primary data using the help of SPSS 25.0 software data analysis tools. The subjects of this study are 78 respondents who use Grab online transportation services with a data collection method using questionnaire distribution. In addition, secondary data is obtained from indirect data sources such as articles and journals. The results of the analysis show that price variables have a positive and significant effect on people's interest in using Grab online transportation services. Meanwhile, the variable of advertising promotion has no effect on people's interest in using Grab online transportation services. The test simultaneously produced prices and advertising promotions that had a positive and significant effect on people's interest in using Grab online transportation services.